Networked NPOs in the global South: knowledge management and organisational effectiveness - Akinsanmi, Titilayo Olujumoke (My University, 2011)
This research sought to understand the knowledge management (KM) practices in use by networked southern non-profit organisations (NPOs), which directly or indirectly impact on their effectiveness. It explores the realm of NPOs, and the concepts of organisational effectiveness (OE) and KM, with the aim of identifying their interrelationships from a theoretical and practical perspective. The three organisations studied are the Association for Progressive Communications (APC), South Africa NGO Network (SANGONet) and Women’s Network (Women’sNet). Using a conceptually formulated research framework, data gathered was analysed to examine the KM concepts of people capacity, systems and procedures, information and knowledge flow and stakeholder relations within and across all three case studies and their use of information and communications technologies (ICTs) as an enabler. The research concludes with an integrated framework, an addition to the existing body of knowledge on KM theory with key elements for a KM system for effectiveness for networked southern NPOs.
Keywords: Knowledge management; Organisational effectiveness; Nonprofit organisations